x-(-3.3)/-3=-2.9

Simple and best practice solution for x-(-3.3)/-3=-2.9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-(-3.3)/-3=-2.9 equation:


x in (-oo:+oo)

x-(-3.3/(-3)) = -2.9 // + 2.9

x-(-3.3/(-3))+2.9 = 0

x-1.1+2.9 = 0

x+1.8 = 0 // - 1.8

x = -1.8

x = -1.8

See similar equations:

| -1.5x-2=-.5x-2 | | (y^5x^2)/(y^4x^6) | | z-(-3.3)/3=2.9 | | z-3.3/-3=-2.9 | | 3x-8t=-8 | | 5/6*-6/7 | | 2x+7+10=11x | | 1.7(r+1)=6.8 | | 9-4(2x-1)=45-4x | | (-3-7)+(4+7)= | | -152=4(-8+5m) | | b/9=a | | b/9=8 | | 38n+1=25 | | 3=-4/w-7 | | 3(-5a+9)-2(4a+6)= | | 5.25(2)+3.25=10.25+1.75(2) | | 6x^3-12x^2+10x-20=0 | | -10w+2=2w+18 | | 13x+11=12x+3 | | 2(4x+7)+6x=5(x+10) | | -20+n=3.50 | | (6d+5)-(23d)= | | 5/4-1/3x1/2 | | 11=2x-11 | | -34+2x-7x=76 | | -5x+12=-12x+-12 | | 9-1/3a=-4 | | .25n=-12 | | 2x-9+x+3=-27 | | 4x-3=2(X+13) | | 2x-9+n+3=-27 |

Equations solver categories